Correlation between personality traits and coping strategies of young adults in India - Jaiswal, Anushka; Pandey, Neerja; Sarraf, Seema R (The Scientific Temper, 2023)
The present work aims to investigate the correlation between personality traits and coping strategies among young adults in India. Correlational and ex-post facto research designs were employed on a sample of 126 young adults (61 males and 65 females) between 18 to 35 years old. Personality traits and coping strategies were measured using NEO five-factor inventory and coping strategies. It was hypnotized that (a) There will be a significant correlation between personality traits and coping strategies of young adults. (b) There will be significant differences in coping strategies between young adult males and females. (c) There will be a significant difference in personality traits between young adult males and females. The data was analyzed using Pearson correlation and t-tests. Results demonstrated a significant correlation between the two variables. Additionally, a significant difference between males and females has been found in behavior avoidance coping strategies and personality traits of openness and agreeableness.